Adsorption based downstream processing approach for penicillin V from a Penicillium chrysogenum BIONCL I22 culture filtrate - Mishal, Bela H.; Das, Sancharini; Mahajan, Vaishnavi N.; Dharne, Mahesh S.; Joshi, Rakesh S.; Giri, Ashok P. (ACS Omega, 2024)
Penicillin V (phenoxy methyl penicillin) is highly sought after among natural penicillins because of its exceptional acid stability and effectiveness against common skin and respiratory infections. Given its wide-ranging therapeutic uses, there is a need to establish a greener method for its maximum recovery to reduce the carbon footprint. Here, we have identified and validated optimized operational conditions for resin-based penicillin V recovery. It was observed that Amberlite XAD4 had the highest penicillin V hydrophobic adsorption capacity among the other screened resins. Kinetic and isothermal studies using linear and nonlinear regression analysis showed that the adsorption process well fitted with pseudo-second-order kinetics (R-2 = 0.9816) and the Freundlich adsorption isotherm model (R-2 = 0.9871). Adsorption equilibrium was attained within 4 h, while maximum adsorption was observed at 3 mg/mL penicillin V concentration. Furthermore, the optimized extraction protocol was compared with the conventional butyl acetate-based downstream processing. Under optimum conditions resin-based penicillin V recovery was 2-fold higher as compared to the solvent extraction method and the resin could be reused for over six cycles without compromising the yield. These findings signify substantial progress toward the development of an environmentally sustainable approach for penicillin V recovery and a potentially viable method for extractive fermentation.